Komparatif Kontruksi Isu pada Berita Pengangkatan Basuki Tjahaja Purnama sebagai Komisaris Utama Pertamina: Analisa Framing pada berita Kompas dan Media Indonesia - sugeng wahjudi; Andreas Praditya Tegar Pradana (Jurnal Spektrum Komunikasi, 2020)
The issue of the appointment of Basuki Tjahaja Purnama as Pertamina's Chief Commissioner has been hot news by the media. Mass media which is a channel of mass communication has a great power to create public opinion. That is because in carrying out their news, the media are believed to have constructed reality to suit the ideology of the media. The author analyzed Harian Kompas and Media Indonesia in reporting on this issue. This study uses Pan and Kosicki Framing Analysis with a constructivist paradigm because the writer wants to see how the two media construct a phenomenon. The character of this research is comparative because the author wants to compare the differences in the viewpoints of the two print media. The results obtained from this study found that Harian Kompas appeared to be more credible and neutral in its reporting. This can be seen from the completeness of the news element, the use of supporting data in conveying the facts, the use of more than two sources, and the use of more neutral language. While Media Indonesia seems less credible and slightly biased towards the figure of Basuki Tjahaja Purnama. This can be seen from the incomplete elements of the news, the lack of data and sources, and the use of language that seems to support the figure of Basuki.